FGF10 ameliorates lipopolysaccharide-induced acute lung injury in mice via the BMP4-autophagy pathway - Kong, Xiaoxia; Lu, Liling; Lin, Daopeng; Chong, Lei; Wen, Shunhang; Shi, Yaokai; Lin, Lidan; Zhou, Liqin; Zhang, Hongyu; Zhang, Hailin (Frontiers in Pharmacology, 2022)
Introduction: Damage to alveolar epithelial cells caused by uncontrolled inflammation is considered to be the main pathophysiological change in acute lung injury. FGF10 plays an important role as a fibroblast growth factor in lung development and lung diseases, but its protective effect against acute lung injury is unclear. Therefore, this study aimed to investigate protective effect and mechanism of FGF10 on acute lung injury in mice. Methods: ALI was induced by intratracheal injection of LPS into 57BL/6J mice. Six hours later, lung bronchoalveolar lavage fluid (BALF) was acquired to analyse cells, protein and the determination of pro-inflammatory factor levels, and lung issues were collected for histologic examination and wet/dry (W/D) weight ratio analysis and blot analysis of protein expression. Results: We found that FGF10 can prevent the release of IL-6, TNF-α, and IL-1β, increase the expression of BMP4 and autophagy pathway, promote the regeneration of alveolar epithelial type Ⅱ cells, and improve acute lung injury. BMP4 gene knockdown decreased the protective effect of FGF10 on the lung tissue of mice. However, the activation of autophagy was reduced after BMP4 inhibition by Noggin. Additionally, the inhibition of autophagy by 3-MA also lowered the protective effect of FGF10 on alveolar epithelial cells induced by LPS. Conclusions: These data suggest that the protective effect of FGF10 is related to the activation of autophagy and regeneration of alveolar epithelial cells in an LPS-induced ALI model, and that the activation of autophagy may depend on the increase in BMP4 expression.